Estudio de la gestión de operaciones para la mejora continua de la empresa Industria de la Hebilla S.A.C. - Araujo Matta, Christian Yovanni (2022)
This thesis deals with the study of the operations management of the company Industria de la Hebilla S.A.C. to improve the company's performance through the implementation of a continuous improvement system. The current state of the organization is taken as the basis for analysis, as well as information obtained about other competing businesses to carry out a deeper study that includes different realities and proposes solutions to problems that could occur in this type of company. In the study, the knowledge acquired in different courses taken during the university career was applied, integrating tools to carry out a powerful analysis and proposal. The proposed improvement system, although it was developed for a particular company, can be adapted and applied in others of the same line or a similar one that seek to better manage their operations, integrating processes and establishing more exhaustive control methods to ensure the quality of your products or services. The control and evaluation of the results is the most important part of the administrative and strategic process because it allows to show how well the established objectives are met in relation to what is expected by the company. It is from the information obtained at this point that improvement actions can be taken to bring the results towards the required ideal or try to get as close as possible. In the thesis it was obtained that it is necessary to take improvement actions in the current work methods on the planning, organization and control in the areas, periodically evaluating the performance and relying on technological tools that facilitate the flow of information. Applying administrative and basic tools for continuous improvement, on the one hand, allows for better organization and explanation of the work and, on the other hand, facilitates the analysis and solution of the problems presented. The key points of each process must be identified to obtain data and convert it into information.